Astrid the Astronaut: Hydroponic Hijinks - Book 3 - Neal, Rie; Shipman, Talitha (New York : Aladdin, 2022)
When members of the Shooting Stars and Petite Picassos team up for a combined STEM and art project, Astrid is torn between her best friend, Hallie, and her arch-rival, Pearl, until she overcomes her initial suspicions and realizes being a good teammate is more about working together than winning.
Ages 6 to 9.
Keywords: After school programs -- Juvenile fiction; Clubs -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Hearing impaired -- Juvenile fiction; After-school programs -- Fiction; Clubs -- Fiction; Cooperativeness -- Fiction; Hearing impaired -- Fiction; Novels